Preparation and characterization of LiNi0.8Co0.2O2/PANI microcomposite electrode materials under assisted ultrasonic irradiation - Mosqueda, Y.; Perez-Cappe, E.; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Ries, A.; Cilense, M.; Nascente, PAP; Aranda, P.; Ruiz-Hitzky, E. (Elsevier B.V., 2006)
A preparation method for a new electrode material based on the LiNi0.8Co0.2O2/polyaniline (PANI) composite is reported. This material is prepared by in situ polymerization of aniline in the presence of LiNi0.8Co0.2O2 assisted by ultrasonic irradiation. The materials are characterized by XRD, TG-DTA, FTIR, XPS, SEM-EDX, AFM, nitrogen adsorption (BET surface area) and electrical conductivity measurements. PANI in the emeraldine salt form interacts with metal-oxide particles to assure good connectivity. The dc electrical conductivity measurements at room temperature indicate that conductivity values are one order of magnitude higher in the composite than in the oxide alone. This behavior determines better reversibility for Li-insertion in charge-discharge cycles compared to the pristine mixed oxide when used as electrode of lithium batteries. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: PANI; Ni-Co mixed oxides; organic-inorganic composites; electrode materials; lithium batteries